Gambaran Tekanan Darah dan Profil Lipid Pada Pasien Stroke Iskemik Akut - Akhbar Fauzan Nainggolan; Chairil Amin Batubara; Ridwan Balatif (Faculty of Medicine, Universitas Andalas, 2021)
Objective: To determine the description of blood pressure and lipid profile of patients with ischemic stroke who were hospitalized at Haji Adam Malik General Hospital, Medan. Methods: This study used a descriptive method with a cross-sectional approach. The sample in this study were patients with ischemic stroke who were treated at the Haji Adam Malik General Hospital. Data was taken using medical records. The variables collected were gender, age, blood pressure and lipid profile. Results: A total of 80 patients with ischemic stroke were included in this study. Most patients with ischemic stroke are above the age of 50 years with the proportion of sex both male and female is the same. 73.75% of patients with ischemic stroke have hypertension. From the lipid profile, 57.5% of patients had total cholesterol above normal, 71.25% of patients had triglycerides within normal limits, 73.7% of patients had low HDL levels and 65% patients had LDL levels above normal. Conclusion: Most stroke patients in this study had hypertension, had total cholesterol levels above normal, had normal triglyceride levels, had low HDL levels and had LDL levels above normal.